A Low‐Cost NiO Hole Transfer Layer for Ohmic Back Contact to Cu2O for Photoelectrochemical Water Splitting. Issue 39 (8th August 2017) - Wei, Yijia; Chang, Xiaoxia; Wang, Tuo; Li, Chengcheng; Gong, Jinlong
Abstract: Cuprous oxide (Cu2 O) photocathode is reported as a promising candidate for photoelectrochemical water splitting. The p‐type Cu2 O usually forms a Schottky junction with the conductive substrate due to its large work function, which blocks the collection of photogenerated holes. NiO is considered as one of the most promising hole transfer layers (HTL) for its high hole mobility, good stability, and easy processability to form a film by spin coating. The utilization of NiO HTL to form an Ohmic back contact to Cu2 O is described, thus achieving a positive onset potential of 0.61 V versus reversible hydrogen electrode and a twofold increase of solar conversion efficiency. Abstract : NiO hole transfer layer prepared by spin coating on F:SnO2 followed by a postannealing process is introduced to form an Ohmic back contact to a Cu2 O photocathode, which can extract photogenerated holes from Cu2 O, thus improving the charge carrier separation at the back contact efficiently. This constitution provides an example for enhancing the performance of photoelectrodes via introducing low‐cost back contact materials.